2015
DOI: 10.1016/j.jembe.2014.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Ontogenetic habitat shifts of green turtles (Chelonia mydas) suggested by the size modality in foraging aggregations along the coasts of the western Japanese main islands

Abstract: a b s t r a c tTo understand the life histories and ontogenetic habitat utilization of green turtles along the coasts of the western Japanese main islands, we collected size frequency and genetic data of green turtles captured by pound nets in three foraging grounds (FG): Nomaike (n = 38), Muroto (n = 93), and Kumano-nada (n = 31), and compared their natal origins among different size classes. Population genetic analyses based on an 820-bp fragment of mitochondrial DNA showed that the three FG were part of a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 43 publications
2
12
0
Order By: Relevance
“…If this is the case, then this is of great concern, and could represent a wider problem in the region. Alternatively, the observed absence of mid-size green turtles could reflect developmental transience as has been found in other populations (Hamabata et al 2015). Small juveniles may recruit to neritic developmental grounds, to later migrate to other coastlines as mid-size juveniles for the final stages of development prior to adulthood such as the wellknown adult foraging grounds off the coasts of North Africa and Turkey (Stokes et al 2015).…”
Section: Uncommon Size Classesmentioning
confidence: 82%
“…If this is the case, then this is of great concern, and could represent a wider problem in the region. Alternatively, the observed absence of mid-size green turtles could reflect developmental transience as has been found in other populations (Hamabata et al 2015). Small juveniles may recruit to neritic developmental grounds, to later migrate to other coastlines as mid-size juveniles for the final stages of development prior to adulthood such as the wellknown adult foraging grounds off the coasts of North Africa and Turkey (Stokes et al 2015).…”
Section: Uncommon Size Classesmentioning
confidence: 82%
“…Foraging green turtles in the South China Region and Ryukyu Islands of Japan shared similar natal rookeries in Southeast Asia, Yaeyama Islands of Japan, Micronesia and the Marshall Islands in the West Pacific (Nishizawa et al, 2013;Ng et al, 2017;Hamabata et al, 2018). Several studies confirmed that northern foraging green turtles in mainland Japan were primarily contributed by Japanese rookeries in the Ogasawara and Ryukyu Islands (Nishizawa et al, 2013;Nishizawa et al, 2014b;Hamabata et al, 2015, Hamabata et al, 2016, Hamabata et al, 2018. Whereas the southern foraging aggregations around the Yaeyama and Ryukyu Islands were sourced from the Yaeyama and Ogasawara Islands, and various Pacific rookeries in the West Pacific and Indian Oceans and Southeast Asia (Nishizawa et al, 2013;Hamabata et al, 2018).…”
Section: Population Genetics and Connectivity Of Green Turtlesmentioning
confidence: 92%
“…Haplotype data associated with nesting populations were collected from Yaeyama (Nishizawa et al, 2011), the central Ryukyus (Hamabata et al, 2009(Hamabata et al, , 2014, and Ogasawara Islands (Nishizawa et al, 2013;Hamabata et al, 2020). Haplotype data for the foraging aggregations were collected from Yaeyama (Nishizawa et al, 2013;Hamabata et al, 2023), Okinawajima (Nishizawa et al, 2013;Hayashi and Nishizawa, 2015;Hamabata et al, 2018), Nomaike, Muroto, Kumano-nada (Hamabata et al, 2015), Oita (Kudo et al, 2021), Kanto (Nishizawa et al, 2013), and Sanriku (Nishizawa et al, 2014). We expanded the existing haplotype dataset by including new samples from nesting sites and sites where turtles were present while foraging or in water.…”
Section: Green Turtlesmentioning
confidence: 99%